Oscillated Variable Neighborhood Search for Open Vehicle Routing Problem - Güler, Bekir; Şevkli, Aişe Zülal (Neural Information Processing, 2015)
Open Vehicle routing problems is a variant of Vehicle Routing Problem, in which vehicles don’t return the depot after serving the customers. In this study, we proposed a cluster first-routed second based algorithm. We combined Kmeans and Variable Neighborhood Search in this algorithm. Our proposed algorithm achieves the best know solutions within a reasonable time for all well-known small and medium scale benchmarks.